1998
DOI: 10.1007/s11746-998-0181-x
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic interesterification of lard and high‐oleic sunflower oil with Candida antarctica lipase to produce plastic fats

Abstract: Lard and high-oleic sunflower oil (Trisun ® Extra) were interesterified at 55°C for 24 h with SP435 lipase from Candida antarctica to produce plastic fats. As the amount of trisun increased, percentage free fatty acid, unsaturated fatty acid/saturated fatty acid value, oxidizability, and the amount of 18:1 found at the sn-2 position of triglyceride products increased. Differential scanning calorimetry showed that the lowmelting components in the product contained more 18:1 than the high-melting components. A 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…Such interesterification increases concentration of unsaturated fatty acids thus greatly improves the nutritional and functional properties of interesterified products 7,8 . Interesterification also stabilizes the polymorphic β form of interesterified product preventing it from sandiness 4 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Such interesterification increases concentration of unsaturated fatty acids thus greatly improves the nutritional and functional properties of interesterified products 7,8 . Interesterification also stabilizes the polymorphic β form of interesterified product preventing it from sandiness 4 6 .…”
Section: Introductionmentioning
confidence: 99%
“…A Supelcowax-10 capillary GC column (0. 25 Triacylglycerol molecular species were analyzed using an HPLC apparatus (Jasco, Tokyo, Japan) equipped with a model 980 HPLC pump, a 930 RI detector, and an 807-IT integrator using a Chrompack ChromSphere Lipids analytical silver-impregnated column (4.6 mm i.d.×250 mm length, stainless steel, 5 mm particle size; Varian, Bridgewater, NJ, USA) (12). The mobile phase was 0.5% acetonitrile in nhexane with isocratic operation at a flow rate of 1.0 mL/ min at 35 o C. During the interesterification reaction, an aliquot was withdrawn from the reaction mixture using a microsyringe and injected into the HPLC for triacylglycerol analysis.…”
Section: Methodsmentioning
confidence: 99%
“…111 When lard and high-oleic sun¯ower (60:40) were interesteri®ed (Candida antarctica, 55°C, 24 h) the product was superior to that obtained by blending alone and had solid content resembling that of a soft margarine at a range of temperatures. 112 From the examination of a ternary mixture of canola oil, hydrogenated canola oil, and palm stearin Cho and deMan 113 concluded that the interesteri®cation product crystallised in the desirable b' form and could be used to produce margarine with trans levels lower than conventional products made from hydrogenated oils even though trans acids were still present.…”
Section: (Iii) Margarine and Shorteningmentioning
confidence: 99%